Roads to success - Heller, Robert (New York : Dorling Kindersley Pub., 2001)
This book is food for thought, its rich diversity emphasizes that there is no one right path to managerial achievement , no universal panacea.
Includes Index.
Includes bibliographical references: p. 848-849.
II 23/01/2019
Ref.
Keywords: Businessmen; Success in business